Analysis of Irrigation System Performance Based On Application of Elektronik Pengelolaan Aset dan Kinerja Sistem Irigasi (ePAKSI) In Kembang Irrigation Area In Majalengka District - Ipa Hafsiah Yakin (PT Inovasi Pratama Internasional, 2023)
Food security is one of the achievement targets both at the national and regional levels. The performance of the irrigation system is an integration of 5 pillars which include infrastructure, water, management, management institutions, and human resources. To determine the performance of the irrigation system, an instrument needed to assess the performance of an irrigation system. Kembang Irrigation Area located in Sukahaji District, Majalengka Regency. The lack of optimal performance of the irrigation system of the Kembang Irrigation Area can be seen from its planting productivity. The research method used is a qualitative method. Researchers conducted several methods to collect research data on the performance of the Kembang Irrigation Area, irrigation system through several data collection techniques, namely through observation using the ePAKSI application, interviews, and documentation. The conclusion of this study that Kembang Irrigation Area has an overall irrigation system performance index of 43.19% (scale 0 – 100%). Based on regulation, the irrigation system performance index < 55% it has poor performance, needs immediate handling. It can overcome problems in Kembang Irrigation Area through various efforts, Rehabilitation and Development of the Irrigation System, proposing the needs of Water Resources employee, preparation of the Irrigation Manual Book, implementation of training regularly.